Kepuasan Konsumen Tanaman Anggrek di Kebun Sekar Gumilang Desa Ketenger Kecamatan Baturraden Kabupaten Banyumas - Ilham Wardoni; Sri Widarni; Djeiny Kusnaman (Program Studi Agribisnis INSTIPER Yogyakarta, 2023)
Orchid is an ornamental plant has an aesthetic value in flowers. Everyone likes orchids to decorated for outside or inside of the house. One of the gardens sells various types of orchids is Sekar Gumilang Orchid Garden. This research to determine level of customer satisfaction orchid, to find out attributes give highest and lowest satisfaction, and to formulate a strategy for developing Orchid business. The research was conducted from July to August 2022. The object of the research was consumers who were buying or had bought orchids at the Sekar Gumilang orchid garden. Questionnaire data analyzed using Customer Satisfaction Index (CSI), Importance Performance Analysis (IPA) and Pyramid analysis consumer loyalty. The results showed the consumer satisfaction level is 68.01% was included in the satisfied criteria. The highest attribute performance is being active in promotions social media, while the lowest attribute performance is the absence of complete and clear signage or road signs. The development strategy needs to make signboards or road signs. The development strategy is needs make signboards or directions to location of the garden. The level of customer loyalty is mostly satisfied, but all consumers are not be loyal because the percentage of committed buyers is smaller than switcher buyers